Bhishma as a Superman in the Mahabharata - Bhandari, Sabindra Raj (The Outlook: Journal of English Studies, 2020)
This article explores and interprets Bhishma, one of the great heroes in the classical epic the Mahabharata, from the perspective of superman that the great philosopher Nietzsche postulates in his great work Thus Spoke Zarathustra. The superman is one of the alluring concepts in the domain of entire philosophy. He has his own ideals, standards, and thus becomes the creator of his own self. Sacrificing himself for the morals and dignity, he becomes an emblem for the righteousness, truth, and virtues. He stands for the sake of justice and righteousness, and suffers to rise himself even beyond the dualities of the world. Nietzsche’s superman is a man transcendent. Bhishma, in the great epic the Mahabharata, also establishes his own values. He suffers a lot, but does not surrender. As a superman, the more difficulties he faces, the more he fills himself with new vibrations and vitalism in his life. His great pledge and his self sacrifice for the truth really transform him into a superman. Therefore, the creative evolution of Bhishma mirrors the genuine ideals of the superman. This paper applies the qualitative approach, and attempts to add a new dimension while interpreting and exploring the ideations of superman in one of the great heroes from the longest epic the Mahabharata.